Forests for the future local strategies for forest protection, economic welfare, and social justice - Wolvekamp, Paul 1961- (Zed Books, 1999)
"Many of the world's people depend on forests for their daily survival. This book addresses the question: how can local and indigenous communities maintain the balance between their societies and their forest environments when faced with increasing external pressures, rising populations and a growing demand for cash income and for basic needs to be met." "Given the current impasse in international forest negotiations and the inertia of most governments, it is crucially important to pay regard to and support such local citizens' initiatives. One of the things that distinguishes this book is that its authors belong to the local groups involved in these efforts. It presents their experiences and recommendations on how to re-establish community control over forest lands and preserve them for the future."--Jacket